The use of biologically active substances in the technology of growing tomato F1 Sherami in protected ground conditions - N. V. Filippova; G. B. Demyanova-Roy (Овощи России)
Relevance. The interest of vegetable producers in small-fruited tomato hybrids has been increasing in recent years. This is due to the high commercial qualities of fruits that do not crack, contain 3 times more sugars than large-fruited tomatoes, and their range of use for canning and salads has also been expanded.Goal: to identify effective options for the use of biologically active substances in conditions of extended turnover of winter greenhouses on tomato plantings F1 Sherami.Methods. Research was aimed at studying the effect of biologically active substances – sodium selenate at a concentration of 10-5, natural coniferous concentrate (2 mg/l), EpinExtra (0.2 mg/l) and their double and triple combinations on the productivity of cherry tomatoes F1 Sherami. The treatment of plants was carried out 4 times during the growing season – after picking, when planting seedlings in a permanent place, when pouring the first brush and during the mass harvest.Results. As a result of research, it was found that the use of the above drugs increases the productivity of tomato plants of the Sherami hybrid. The maximum yield according to the results of 2018 and 2019 was obtained on the variant using sodium Selenate + KHN + Epin-extra and averaged 288.1 t/ha. Also, the use of BAS had an effect on the content of dry matter, sugars and macronutrients.Conclusion. The effect of preparations of biologically active substances positively affected the growth and development of plants. The variation of the yield increase compared to the control ranged from 5.2 to 17.2 t/ha. The maximum yield of the Sherami hybrid tomato was obtained on the variant using sodium Selenate + KHN + Epin-extra, the increase was 19 t/ha, which made it possible to obtain an appropriate income level of more than 272 thousand rubles/ha.